Globalization is not a Phenomenon of Today - Dr. Ahmed Elhaj Omer Hamed (Journal of Arts, Literature, Humanities and Social Sciences, 2024)
Globalization is the process by which knowledge, information, services and goods spread worldwide. The term is referred to in the field of trade and cultural and economic systems. The world becomes more globalized when countries become politically, culturally and economically interwound. Many people think of globalization as phenomenon of the twentieth century, but it is a process which has been happening for millennia. The process can be traced through history and reviewing different cultures and their interactions.